Fine-Tuning the TGFβ Signaling Pathway by SARA During Neuronal Development - Rozés-Salvador, Victoria; Wilson, Carlos; Olmos, Cristina; Gonzalez-Billault, Christian; Conde, Cecilia (Frontiers in Cell and Developmental Biology, 2020)
Neural development is a complex process that involves critical events, including cytoskeleton dynamics and selective trafficking of proteins to cellular destinations. In this regard, Smad Anchor for Receptor Activation (SARA) is an early endosome resident protein, where perform trafficking- associated functions. In addition, SARA also mediates cell signaling, including the TGFβ-dependent pathway. Accordingly, SARA and TGFβ signaling are required for proper axonal specification and cortical migration of neurons, unveiling a critical role for neuronal development. However, the cooperative action between the TGFβ pathway and SARA to this process has remained understudied. In this work, we show novel evidence suggesting a cross-talk between SARA and TGFβ pathway needed for proper polarization, axonal specification, growth and cortical migration of central neurons both in vitro and in vivo. Using microscopy tools and cultured hippocampal neurons, we show a local interaction between SARA and TβRI (TGFβ I receptor) at endosomes. In addition, the loss of function of SARA, induced by the expression of the dominant-negative SARA-F728A, over-activates the TGFβ pathway, most likely by conserving the TβRI phosphorylated. Consequently, SARA-mediated activation of TGFβ pathway impacts on neuronal development, promoting axonal growth and cortical migration of neurons during brain development. Moreover, our data suggests that SARA basally prevents the activation of TβRI through the recruitment of the inhibitory complex PP1c/GADD34 in polarizing neurons. Together, these results propose that SARA is a negative regulator of the TGFβ pathway, being critical for a proper orchestration for neuronal development.